Documenting baseline value chains of Palau's nearshore and offshore fisheries prior to implementing a large-scale marine protected area. (July 2020) - Dacks, Rachel; Lewis, Staci A.; James, Philip A.S.; Marino, Lincy L.; Oleson, Kirsten L.L.
Abstract: Large-scale marine protected areas (LSMPAs) are increasingly enacted to manage marine resources and meet international targets, yet their socio-economic impacts are not well documented. In 2015, Palau passed the Palau National Marine Sanctuary (PNMS) Act, which will close 80% of its exclusive economic zone to fishing by 2020. An assessment of Palau's fisheries value chains can provide a baseline to assess the policy's impacts on the domestic market. A literature review and key informant interviews were conducted between August 2016 and June 2018 to: (i) estimate the current market size and structure; (ii) document the volumes, forms, and prices of fish throughout the market chain; and (iii) estimate fish consumption by different end consumers. The analysis finds the vast majority of reef fish are locally consumed by residents and the vast majority of tuna are exported internationally. Tourist consumption of reef fish (estimated for the time frame of the study during which tourist numbers varied considerably), anecdotally highlighted as a threat to reef fisheries sustainability, is relatively small. About half of resident reef fish consumption is non-commercial, highlighting the potential of non-market-based interventions. Commercial fish supply was reportedly inconsistent, a current challenge, but potential opportunity for a new, offshore domestic fishery. Finally, prices have remained stable, a characteristic of the market that may be attributed to the importance of social relationships in Palauan culture. Our results suggest key actions for PNMS implementation, can be used to evaluate future impacts of the PNMS, and provide planning insights for LSMPAs regionwide. Highlights: Volumes and prices are estimated for nearshore and offshore fisheries value chains. Proportion of reef fish catch consumed by tourists is very low (1.9-4.0%). Large volume of reef fish used non-commercially, for customary events and export. Importance of social relations in Palauan culture may be driver of static fish prices.